Diverse Experiences Lead to a Career in Applied Research: A Conversation With Ann Daunic. (November 2021) - Worth, Megan R.; Poling, Daniel V.
Dr. Ann P. Daunic is an emeritus scholar in the Special Education, Psychology, and Early Childhood Studies programs in the College of Education at the University of Florida (UF). A graduate of Ohio Wesleyan University, she has a doctorate in special education from UF and a master's of science degree in psychology from Tufts University.